2017
DOI: 10.1111/cla.12193
|View full text |Cite
|
Sign up to set email alerts
|

The geometry of gender: hyper‐diversification of sexual systems in Urtica L. (Urticaceae)

Abstract: Urtica L. (Urticaceae) is generally reported as a genus of monoecious and dioecious taxa. However, the gender information found in the literature does not at all reflect the actual diversity of gender patterns in Urtica. Dioecy appears to be truly absent from Urtica, but otherwise there has been a major diversification in the geometry of gender and no comparable patterns exist in other plant groups. Thus, we here define technical terms for all unique architectural types of monoecy found in Urtica and closely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Urtica dioica is characterized by huge variation mirrored by a high number of intraspecific taxa distinguished either solely based on morphological characters (e.g. various types of indumentum [54–56]) or with consideration for sexual morphs (predominantly stochastically occurring [54, 55, 57]). Finally, polyploidy is a truly substantial source of variation in U. dioica .…”
Section: Introductionmentioning
confidence: 99%
“…Urtica dioica is characterized by huge variation mirrored by a high number of intraspecific taxa distinguished either solely based on morphological characters (e.g. various types of indumentum [54–56]) or with consideration for sexual morphs (predominantly stochastically occurring [54, 55, 57]). Finally, polyploidy is a truly substantial source of variation in U. dioica .…”
Section: Introductionmentioning
confidence: 99%
“…gracilis) subspecies have been reported [52]. Große-Veldmann and Weigend [53] also suggested that no strict dioecious species belong to the genus Urtica. Urtica dioica and all its subspecies are polygamous, with Urtica dioica subsp.…”
Section: Biology Ecology and Reproductionmentioning
confidence: 99%
“…Stinging nettle ( Urtica dioica L., Urticaceae family) is a wild-growing herbaceous perennial occurring almost all over the world. It grows mainly on damp and nitrogen-rich soil at partly shaded sites, including meadows, forests edges and brushwoods [ 1 , 2 , 3 , 4 ]. The nettle is highly polymorphic in terms of its ploidy level, developmental traits and chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…So far, plenty of subtaxa, including subspecies, morpho- and ecotypes, varieties and hybrids have been recognized within the species [ 5 , 6 ]. Thus, it is treated as a complex taxonomic group described collectively as U. dioica sensu lato [ 1 , 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%